THE DIFFERENCE BETWEEN DIGITAL EVIDENCE AND EVIDENCE IN DIGITAL FORM - Rashkovsk, Dragi; Rashkovska, Veronika (University Ss. Cyril and Methodius in Skopje, 2025)
At first glance, the two concepts—digital evidence and evidence in digital form—may seem synonymous. However, while all digital evidence can indeed be classified as evidence in digital form, not all evidence in digital form qualifies as digital evidence. This distinction leads to the conclusion that digital evidence constitutes a subset of evidence in digital form. Yet, even this conclusion is not entirely absolute, as for digital evidence to be admissible in judicial proceedings, it must satisfy specific prerequisites. These are not merely technical prerequisites—which fall outside the scope of this paper—but primarily legal prerequisites that determine whether “ordinary” digital records may be transformed into “admissible” digital evidence capable of serving as the basis for a court ruling. Digital evidence, as a specific category of evidence in digital form, is distinguished from other types of digital-form evidence by the presence of metadata, which serves to substantiate many of its inherent properties. In the absence of such metadata, digital evidence is reduced to mere evidence in digital form, lacking the distinctive qualities that render it probative and admissible. Metadata is often described as “data about data.” These are digital records which, although sometimes invisible or, if visible, incomprehensible to the ordinary user of information technology, provide the unique “fingerprint” of a digital record. Much like a fingerprint left on a physical piece of evidence, metadata authenticates and preserves the integrity of the digital record. Without such a “fingerprint,” one might say that “the glass is shattered on the floor, but it cannot be determined which of those present threw it.” Metadata thus constitutes the DNA of a digital record. Although technical in its essence, metadata is not merely a technical concept. It also functions as a legal category, explicitly addressed in numerous legal instruments regulating the collection of digital evidence, which underscores its fundamental importance. One of the objectives of this scholarly paper is to make this legal-technical concept more accessible to legal practitioners—judges, prosecutors, defense attorneys, and others—through illustrative examples and an interpretation of existing international legal norms, thereby enabling them to reason in accordance with relevant international standards. At the same time, by examining domestic (Macedonian) legislation, which addresses this subject within what appears to be a somewhat “forgotten” statute, the paper seeks to highlight the gaps that must be addressed in order to ensure the effective application of these norms. Digital evidence has, by its very nature, always existed in digital form, whereas evidence presented in digital form may have originally existed in written or oral form.
Keywords: digital evidence; evidence in digital form; metadata; digital forensics